Simplicity Betrayed. - PHILLIPS, GEORGE (Communications of the ACM, 2010)
The article discusses computer emulating systems, providing examples of how even a relatively primitive system such as the TRS-80 can prove to have unexpected subtleties and complications which make an exact simulation difficult to achieve. A comparison is drawn to the Java Virtual Machine, which is said to embody related concepts in a more forward-looking context. The code needed to create a correct emulation of a diagonal line is analyzed by way of example, which involves floating-point numbers, central processing unit cycles, and cycle-wasting subroutines.